(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
This brief text on the contributions of J. G. Holland to behavior analysis begins with an acknowledgment of its influence, particularly as to the exercise of countercontrol, in the preparation of my doctoral thesis ten years after. Following, problems of acceptance of behavioral orientation in academic and lay environments observed by Holland are discussed in the light of further evidence. A next part of the text describes and discusses the research conducted as part of the thesis, with emphasis on the production of a handbook of social countercontrol and the evaluation of its use by union, political and community leaders, in terms of qualified informants. Finally, considerations are developed on the possible current socialization of radical behaviorism through the practice of behavioral therapy, as well as through one of the last Skinner’s productions to the lay people.